Etiologic Diagnosis of Chronic Osteomyelitis: a prospective study (2006)
ABSTRACT: Background: Although bone specimens were established 25 years ago as the gold standard for etiologic diagnosis of chronic osteomyelitis, recent studies suggest that nonbone specimens are as accurate as bone to identify the causative agent. We examined concordance rates between cultures from nonbone and bone specimens in 100 patients. Methods: Prospective study conducted at Hospital Universitario San Vicente de Paul, a 750-bed university-based hospital located in Medellín, Colombia. We included patients with chronic osteomyelitis who had been free of antibiotic therapy for at least 48 hours, excluding those with diabetic foot and decubitus ulcers. At least 1 nonbone and 1 bone specimen were taken from each individual and subjected to complete microbiologic analysis. Results: Bone cultures allowed agent identification in 94% of cases, including anaerobic bacteria in 14%. Cultures of nonbone and bone specimens gave identical results in 30% of patients, with slightly better concordance in chronic osteomyelitis caused by Staphylococcus aureus (42%) than by all other bacterial species (22%). However, statistical concordance determined by the Cohen kappa statistic was less than 0 (-0.0092+/-0.0324), indicating that the observed concordance was no better than that expected by chance alone (P>.99). Conclusions: Appropriate diagnosis and therapy of chronic osteomyelitis require microbiologic cultures of the infected bone. Nonbone specimens are not valid for this purpose.